Mengembangkan Sistem Pemantauan Detak Jantung Murah untuk perangkat Android - Muhammad Khalif Fadhilah; Lulu Chaerani Munggaran (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Heart related disease is one of deadly non communicable diseases. In order to detect heart related problems, heart rates must be monitored. Monitoring heart rate can be done with several methods, from stethoscope, to sensors such as PPG and ECG sensors. However, those monitoring can be impractical as it requires doctor visitations. In order to simplify the process, smartwatch is used. Those devices are usually equipped with heart rate monitoring sensors, and many others. However, some previously researched smartwatch-based systems used in monitoring health are cost prohibitive as some requires their own server, high price of smartwatches used, and cumbersome to use. The goal of this research is to build cost effective heart rate monitoring using cheap smartwatches. A proposed system using smartwatch and Android device is used alongside with Whatsapp messaging, with ringtone that plays when emergency situation happened. The message contains GPS location and emergency condition. The resulting system does not require custom made server and nets an acceptable GPS coordinate accuracy outdoors, but not so accurate indoors. It also does not require expensive smartwatches. However, the system requires the device to not be locked due to limitations on Android devices.